VARIABEL-VARIABEL YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PUBLIK SEKTOR NON KEUANGAN - LINDA WIMELDA; AAN MARLINAH (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of this study is to investigate the variables affecting capital structure in non financial public companies. This studyalso have purpose to test and improve consistency of result from prior studies. The samples of this study consist of 120 data from 40 non financial companies that has been listing on Indonesia Stock Exchange for the period 2008 to 2010 by purposive sampling method. This study also use multiple regression method to investigate relation between each independent variable to capital structure. The empirical evidences from this study indicates profitability, firm size, business risk, managerial ownership, and structure of assets have influences to capital structure, but liquidity, growth opportunity, dividend, investment and institusional ownership do not have influences to capital structure.